The Learning Model of O’brien Shot Put for High School Students - Jupianto Sembiring; Hernawan Hernawan; Wahyuningtyas Puspitorini (Universitas Negeri Medan, 2020)
The aim of this research was to produce and develop an O’Brien shot put learning model for high school students. This study used the Research and Development (R&D) method from Borg and Gall, while the subjects in this research and development were students of SMAN 8 DEPOK. In limited trials (small group trials) using 20 students and large group trials using 60 students while the effectiveness test used 40 students. In the test of effectiveness of learning model used the instrument assessment of preparation phase, slip phase, delivery phase and recovery phase skills using a rubric / portfolio (process assessment). Data analysis in this study used the t-test, the results of the initial test before being given the treatment of the O’Brien shot put learning model was equal to 47.70 then after being given the treatment of O’Brien shot put learning model turned up to 83.68. In the significance test of the difference with the application of SPSS Statistics, the t-count result was -85,377 and Sig. (2-tailed) 0.00 <0.05 which means that there were significant differences in the O’Brien Shot Put learning model for high school students before and after the treatment of the O’Brien Shot Put learning model was given. Based on the analysis of the data above it was said that the O’Brien Shot Put learning model for high school students was effective and could improve the learning outcomes of the O’Brien Shot Put for high school students.